2007
DOI: 10.1590/s1679-62252007000200015
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of fish ladders: a bottleneck in Neotropical fish movement

Abstract: Although dozens of fish ladders have been constructed at dams of Brazilian reservoirs, there are few studies evaluating their efficiency as a tool for the conservation of Neotropical ichthyofauna, especially for migratory species. Therefore, the present study evaluated the selectivity of the species that entered and ascended the fish ladder located next to Lajeado Dam (Luis Eduardo Magalhães Hydroelectric Power Plant) on the Tocantins River. Samples were taken monthly from November, 2002 through October, 2003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 8 publications
2
73
0
8
Order By: Relevance
“…A few species represented almost all captures in the facility. This result suggested that most species do not use the ladder, a trend reported in different river basins (Godinho et al, 1991;Oldani & Baigún, 2002;Fernandez et al, 2004;Agostinho et al, 2007a;Makrakis et al, 2007;Agostinho et al, 2009). At Peixe Angical Dam, large numbers of O. niger, P. nigricans, S. rhombeus, L. affinis and a few other species are expected to ascend the ladder successfully.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…A few species represented almost all captures in the facility. This result suggested that most species do not use the ladder, a trend reported in different river basins (Godinho et al, 1991;Oldani & Baigún, 2002;Fernandez et al, 2004;Agostinho et al, 2007a;Makrakis et al, 2007;Agostinho et al, 2009). At Peixe Angical Dam, large numbers of O. niger, P. nigricans, S. rhombeus, L. affinis and a few other species are expected to ascend the ladder successfully.…”
Section: Discussionmentioning
confidence: 70%
“…It cannot be assumed that all fish would successfully pass through the ladder if it was open, but it is probable that the fish inside the ladder would use the facility for dispersal. In addition, field experience and previous monitoring (Agostinho et al, 2007a; have shown that several fish species use ladders in the Tocantins River as an ascending route. Therefore, it was assumed that the fish numbers above and below the screen indicate the number of fish attempting downstream and upstream movements, respectively.…”
Section: Samplingmentioning
confidence: 97%
See 1 more Smart Citation
“…All genetic parameters evaluated here suggest that the populations of the five species showed gene flow. Although the specific geological features of the Corredeira dam facilitates, the potential movement of the fish, the majority of dams built for hydroelectric purposes have a major impact on neotropical fish populations, particularly from the genetic viewpoint (Agostinho et al, 2004(Agostinho et al, , 2007. However, until markers applicable to multi-allelic analyzes are used to confirm our speculation on the cause of gene flow, this conclusion should be treated with caution.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, the fish ladder was built relatively recently. Several studies have demonstrated the inefficiency and selectivity of fish ladders in Brazil (Agostinho et al, 2007;Agostinho et al, 2008). Considering the genetic similarity between the fish sampled upstream and downstream of the Corredeira Dam, and that only P. microstoma was captured in the fish ladder, other factors must influence the maintenance of gene flow.…”
Section: Discussionmentioning
confidence: 99%